Dakon Game as a Culture-Based Strategy for Collaborative Indonesian Learning - Waraulia, Asri Musandi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Interactive and collaborative Indonesian learning is an important need in facing the challenges of conventional learning that tends to be passive and teacher-centered. Traditional games like dakon have great potential to be integrated as a fun, meaningful, and contextual learning medium. This research aims to explore how dakon can be used as an interactive and collaborative vehicle in Indonesian language learning, especially in developing language skills and strengthening cultural values. This study uses a literature review approach by analyzing various relevant research from academic sources. This study reviewed 38 articles related to the integration of traditional dakon games in Indonesian language learning, published between 2010 and 2024 and taken from academic sources such as Google Scholar, SINTA, DOAJ, and Scopus. The analysis was carried out qualitatively with a thematic analysis approach through three main stages: identification of themes using initial code processed with the help of NVivo software, synthesis of content based on the grouping of key findings, and comparison of results between studies to see thematic consistency and variation. The results of the analysis showed that 92% of studies reported improvements in students' cognitive aspects through mastery of vocabulary and text structure after the application of dakon. A total of 87% of studies recorded an increase in student motivation and learning engagement (affective aspect), while 95% of studies documented an increase in social interaction and cooperation between students (social aspect). In addition, 79% of the articles emphasized the role of dakon as a medium for preserving local culture in the context of modern learning. These findings confirm that dakon can be used as an interactive, collaborative, and contextual means of learning.